Vaginal Microbiota and Mucosal Pharmacokinetics of Tenofovir in Healthy Women Using a 90-Day Tenofovir/Levonorgestrel Vaginal Ring - Thurman, Andrea R.; Ravel, Jacques; Gajer, Pawel; Marzinke, Mark A.; Ouattara, Louise A.; Jacot, Terry; Peet, M. Melissa; Clark, Meredith R.; Doncel, Gustavo F. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: A relationship between the vaginal microbiota and tenofovir (TFV) concentrations and activity after topical administration has been previously reported. Objective: CONRAD A15-138 was a randomized, placebo-controlled Phase I study aimed at characterizing the safety, pharmacokinetics (PK) and pharmacodynamics (PD) of TFV and levonorgestrel (LNG) administered through a vaginal ring (IVR) for 90d. Herein we describe changes from baseline in the vaginal microbiota with IVR use and the impact of the vaginal microbiota on mucosal TFV PK. Methods: The study screened 68 participants and randomized 47 (37 TFV/LNG, 10 placebo), assessing the vaginal microbiota by sequencing the V3-V4 regions of 16S rRNA genes prior to IVR insertion and monthly for 3 months. Concentrations of TFV in vaginal fluid (VF), and TFV and TFV-diphosphate (TFV-DP) in vaginal tissue, and modeled PD against HIV-1 in vitro were measured before and after treatment. Results: There were no clinically significant changes in relative abundance of vaginal bacterial phylotypes from pre-insertion baseline at any month among active and placebo IVR users. There were no significant changes in community state type (CST) with IVR use. Participants with diverse, anaerobic CST IVA/B microbiota had higher in vivo release of TFV from the IVR compared to women with Lactobacillus dominated (LbD) microbiota, who had expected in vivo TFV release rates. Median VF TFV concentrations were significantly higher among women with CST IVA/B microbiota in months 1 (3135 ng/mg VF) and 2 (3800 ng/mg). Women with LbD microbiota had significantly higher median VF TFV concentration (1423 ng/mg) and median TFV (103 ng/mg) and TFV-DP (5877 fmol/mg) tissue concentrations versus women with CST IVA/B microbiota at month 3. All women demonstrated a significant increase from pre-insertion baseline of in vitro HIV-1 inhibition by VF (p values<0.05). PD differences in tissue according to CST, however, were not statistically significant. Conclusion: TFV/LNG IVR use did not change the vaginal microbiota nor increase the incidence of CST IVA/B. Vaginal microbiota, and in particular CST IVA/B, possibly through increased vaginal pH, impacted in vivo TFV release and cervicovaginal (CV) PK, but both PK and PD data suggest CV protection against HIV-1. ClinicalTrials.gov (#NCT03279120)